A brief overview on the concept of Palitya w.s.r. premature hair greying. - Makwana, Dhaval Govindbhai; Engineer, Priti; Chudasama, Hardik; Dabhi, Amisha (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: The traditional Indian medical system of Ayurveda employs the term Khalitya ( Hair fall) to describe hair loss, while the premature greying of hair is denoted by the term Palitya ( Hair greying). Khalitya and Palitya are classified as Paitik ( dosha regulating body temperature and metabolic activities) disorders, which originate from the Dosha ( the regulatory functional factors of the body formed by the synchronized interplay between the five basic elements within any living system) known as Pitta. According to Ayurvedic principles, consistent disruption of the Pittadosha ( dosha regulating body temperature and metabolic activities), which represents the body’s heat and metabolism, may result in premature greying of hair. As per Ayurveda principles, the consumption of substances that enhance Pitta can lead to an aggravation of Pittadosha ( dosha regulating body temperature and metabolic activities), which is believed to be a contributing factor in the manifestation of grey hair. Materials and methods: Palitya ( premature greying of hair) information is gathered from many Ayurvedic and modern medical textbooks, magazines, journals, and the internet. It is a review paper with data gathered from all relevant sources. Result: All of the aforementioned formulations were acquired as a result of premature greying of hair. Discussion & Conclusion: Ayurveda has been identified as a viable alternative therapeutic approach for the condition of premature greying that was natural and harmless.